Synovial fluid macrophages are capable of osteoclast formation and resorption. - Adamopoulos, I; Sabokbar, A; Wordsworth, B; Carr, A; Ferguson, D; Athanasou, N (2006)
To determine whether synovial fluid (SF) macrophages isolated from the SF of osteoarthritis (OA), rheumatoid arthritis (RA) and pyrophosphate arthropathy (PPA) joints are capable of osteoclast formation, and to investigate the cellular and humoral factors required for this to occur, SF macrophages (CD14+) were isolated from the knee joint SF from patients with OA, RA and PPA and cultured for up to 14 days with macrophage-colony stimulating factor (M-CSF) and soluble receptor activator for nuclear factor-kappaB ligand (RANKL) or tumour-necrosis factor-alpha (TNFalpha) and interleukin-1alpha (IL-1alpha). Osteoclast differentiation was assessed by expression of tartrate-resistant acid phosphatase (TRAP) and vitronectin receptor (VNR), F-actin ring formation and lacunar resorption. Osteoclast formation and lacunar resorption was seen in RANKL-treated cultures of SF macrophages isolated from OA, RA and PPA joints with the largest amount of resorption noted in RA and PPA SF macrophage cultures. In TNFalpha/IL-1alpha-treated RA and PPA SF macrophage cultures, osteoclasts capable of lacunar resorption were also formed. Lacunar resorption was more extensive in RANKL than TNFalpha/IL-1alpha-treated cultures. These findings indicate that SF macrophages are capable of differentiating into mature osteoclasts capable of lacunar resorption. M-CSF in combination with RANKL or TNFalpha/IL-1alpha was required for osteoclast formation. As inflammatory synovial fluids contain an increase in the number of macrophages and an increase in the amounts of RANKL, TNFalpha and IL-1alpha, these findings suggest that one means whereby bone erosions may form in rheumatoid or crystal arthritis is by differentiation of synovial fluid macrophages into osteoclasts.